Supuestos epistemológicos de la Teoría Política del Común: aportes de los feminismos y de la sociología crítica latinoamericana - Salazar Zarco, Ana Lilia (Diálogos Latinoamericanos, 2025)
This article examines the epistemological assumptions of the Political Theory of the Commons, focusing on the relationship between concrete and abstract labor in capitalist modernity. It analyzes how reproductive and care labor, conceptualized through feminisms and Latin American critical sociology, challenges dominant individualistic and mercantile social forms. These perspectives propose community-based alternatives grounded in interdependence, cooperation, and co-responsibility. Drawing on the contributions of Marx, Federici, Segato, and others, the article discusses the binary logic that characterizes capitalist modernity and its exclusion of many forms of life and labor. Care work is highlighted as a central element for revaluing social and economic relationships and for decolonizing political imaginaries about well-being and social justice. From this reflection, the article advocates an epistemological and political shift that promotes new inclusive, solidaristic social organizations centered on the care of life, especially in Latin American contexts. This paper concludes that integrating feminist perspectives and Latin American critical sociology into the political theory of the commons enriches our understanding of social interdependence and the value of care, proposing a framework that challenges the individualism and commodification inherent in capitalist modernity.